The moderating role of COVID-19 pandemic on the relationship between CEO characteristics and earnings management: evidence from Bangladesh - Mohammad Helal Uddin (Cogent Business & Management, 2023)
This research uses accrual and real earnings management strategies in an emerging economy to evaluate how CEO characteristics (i.e. CEO nationality, duality, and compensation) affect earnings management and how the COVID-19 pandemic modifies this connection. The empirical investigation used annual reports from 2011 to 2021 of 118 listed enterprises in thirteen sectors of non-financial organizations in Bangladesh. The study divided the sample further into COVID-19 pandemic and pre-pandemic periods. Findings show that firms tend to engage less in real earnings management during the COVID-19 pandemic period compared to pre-pandemic period. CEO nationality significantly negatively affects accrual-earnings management, but CEO dualism positively affects real-earnings management. CEO compensation significantly impacts accrual and real earnings management. Finally, COVID-19 moderates the association between CEO compensation and real-earnings management positively. The study's findings contribute to the corporate governance literature by providing insights into the influence of CEO characteristics on earnings management. This is the first study to consider the moderating role of the COVID-19 pandemic on the relationship between CEO traits and earnings management.
Keywords: M10; M12; M14; M41; M48; 650; Bangladesh; CEO characteristics; Covid-19 pandemic; earnings management; emerging economies; listed non-financial organization